GAALSMDA: A Graph Attention-based Fusion Network Integrating Dual Attention and BiLSTM for Microbe-Drug Association Prediction - Xiang, Chunling; Shen, Gaoning; Wang, Lei; Zhu, Xianyou (Current Bioinformatics, 2025)
<span class=
Keywords: Microbe-disease associations